Should there be two genders? The case of intersex people - Pikramenou (Νικολέτα Πικραμένου), Nikoleta (Bioethica, 2015)
Gender refers to all those social, cultural, and psychological traits which are linked to males and females through particular social contexts. Sex makes us male or female and gender makes us masculine or feminine. However, this relatively simple distinction masks a number of problems associated with its usage. It implies that all people can be conveniently placed into unambiguous “either–or” categories. Intersex people are born with characteristics that are in between male and female. Consequently, they often go through a lot of suffering because intersex infants are sometimes subjected to unnecessary medical or surgical treatment that is cosmetic rather that vital for health in order to fit in the gender binary model. Although at least one in every thousand people is born intersex, many countries do not acknowledge their existence. Their rights are also ignored because they don't fit into standard social and medical models. In this article, I will examine the negative effects of this gender binary distinction and justify my arguments by using the example of intersex people.